MANAJEMEN PELAYANAN PUBLIK DALAM PERSPEKTIF ISLAM (Studi di Rumah Sakit Ibnu Sina Kota Pekanbaru) - Muhammad Rachmadi; Muslim Muslim (JURIS (Jurnal Ilmiah Syariah), 2016)
This study aimed at examining the relationship between Islamic values and public services. To achieve the purpose it employed survey research design. The patients in Ibnu Sina Islamic hospital were assigned as respondents and questionnaire was used to assess their perceptions toward the values and the quality services provided by the hospital. The findings showed that 1) the implementation of the Islamic values provided by the hospital was in general was ‘good’,  2) the quality of public services in general was also ‘good’, and 3) the correlation between the implementation of Islamic values and the quality of public services was ‘positive’ (0.458 on Pearson Product Moment index). It can be concluded that the more Islamic values were implemented, the quality of public services tended to be more realized. Theoretically, the finding were expected to yield evidence that there was positive correlation between organizational culture, especially religious values, and organizational performance, especially quality of public services. Practically, the findings encouraged the hospital managers to keep improving their implementation of Islamic values since the of quality of public services tended to increase as well.Kata kunci: nilai-nilai Islam, pelayanan publik, rumah sakit Islam Ibnu Sina